Blood clot parameters: Thromboelastography and scanning electron microscopy in research and clinical practice. Issue 154 (June 2017) - Pretorius, Etheresia; Swanepoel, Albe C.; DeVilliers, Sulette; Bester, Janette
Abstract: Background: Clotting parameters are informative of overall haematological healthiness of an individual. Particularly, clotting parameters can be used as a measure of the degree of pathology of the coagulation system. Thromboelastography (TEG) is a well-known technique that is an important point-of-care method, as well as research method. Scanning electron microscopy (SEM) is a novel research method, but with possible clinical application. However, there are no clear standardized guidelines for TEG and SEM result interpretation. Materials and methods: We have an extensive database of results from TEG of hypercoagulable, hypocoagulable and healthy whole blood (WB) and platelet poor plasma (PPP). These results were generated using citrated PPP or WB, followed by the addition of CaCl2, to initiate clot formation. We also have an extensive and comprehensive database of thousands of clot micrographs, prepared for SEM. We reanalysed all our data to compile a user-friendly guideline for TEG and SEM. We also discuss the effects of different storage times on both WB and PPP. Results: We provide a quick and informative guide that discusses each TEG parameter, in both WB and PPP. Increases or decreases in the various parameters are indicative of either hyper- or hypocoagulability. We also show how hypo- and hypercoagulable clots look like, compared with healthy clots, using SEM analysis of clots created by adding thrombin to PPP. Conclusion: For optimal and speedy interpretation of a patient's coagulation status, it is essential for the clinician to make an informed and precise decision regarding clotting propensity. We believe this guideline will add to the standardization of TEG parameters, and ultimately contribute to the treatment of patients. These guidelines will also allow researchers to standardize their data interpretations and ultimately allow for the use of a global and inclusive database that might be included in precision medicine approaches. Highlights: Blood clot parameters are of great importance in clinical practice and thromboelastography is a point-of-care method. We discuss individual TEG parameters for plasma and whole blood and correlate the parameters with results from scanning electron microscopy. These guidelines will standardize TEG and SEM interpretations that can included in precision medicine approaches.